2021
DOI: 10.1111/bld.12393
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers to optimal diabetes care for adults with learning disabilities: A systematic review

Abstract: Accessible Summary Adults with learning disabilities and diabetes are more likely to have health problems than people with diabetes who do not have learning disabilities. This research had two aims. One was to find out what stops adults with learning disabilities from getting help with their diabetes. The other was to find out what things help them get the best care for their diabetes. We found 12 things that stop adults with learning disabilities from getting good care for their diabetes and 14 things that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…adjustments (Holden & Lee, 2022). Healthcare professionals can be discouraged from appropriately registering all quality indicators due to issues such as high administrative burden in care for people with intellectual disabilities (Weise et al, 2017), low experienced userfriendliness of health information systems, such as the one used in this study (van der Beek, 2016), and difficulties in collaboration across care organisations due to the use of different electronic patient records (Tummers et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…adjustments (Holden & Lee, 2022). Healthcare professionals can be discouraged from appropriately registering all quality indicators due to issues such as high administrative burden in care for people with intellectual disabilities (Weise et al, 2017), low experienced userfriendliness of health information systems, such as the one used in this study (van der Beek, 2016), and difficulties in collaboration across care organisations due to the use of different electronic patient records (Tummers et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties in performing clinical examinations in people with intellectual disabilities (Navas et al, 2019; O'Neill et al, 2019; Pouls et al, 2009; Van De Louw et al, 2009) often result in GPs having to choose which aspects of disease management are most important to tackle short‐term rather than establishing more long‐term goals. On the other hand, information systems may be too elaborate for care for people with intellectual disabilities, and they often do not allow for reasonable adjustments (Holden & Lee, 2022). Healthcare professionals can be discouraged from appropriately registering all quality indicators due to issues such as high administrative burden in care for people with intellectual disabilities (Weise et al, 2017), low experienced user‐friendliness of health information systems, such as the one used in this study (van der Beek, 2016), and difficulties in collaboration across care organisations due to the use of different electronic patient records (Tummers et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of Maine et al (2017), and Holden and Lee's ( 2021) systematic review about the barriers and enablers to optimal diabetes care for adults with intellectual disabilities. Holden and Lee (2021) found that current structured group education courses are not appropriate to the learning needs of adults with intellectual disabilities. Adapted programmes, such as DESMOND-ID for people with type 2 diabetes and intellectual disabilities have been developed (Taggart et al, 2018), but such programmes are not available nationally (Maine et al, 2017).…”
Section: Education and Trainingmentioning
confidence: 98%